2000
DOI: 10.1080/15235882.2000.10162763
|View full text |Cite
|
Sign up to set email alerts
|

A Texas Two-way Bilingual Program: Its Effects on Linguistic and Academic Achievement

Abstract: This study examines a variety of student outcomes in the area of linguistic and academic development and determines whether students enrolled in a two-way bilingual program for a minimum of three year s are achievin g academica lly. Particip ants were native Spanish-speaking and native English-speaking fifth-grade students of Mexican origin. The findings indicate that the majority of students who participated in the two-way bilingual program were performing at academic levels equal to or greater than their non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 11 publications
3
51
0
1
Order By: Relevance
“…One representative study found that TWI students outperformed their peers in math and science as well (Marian, Shook, & Schroeder, 2013). Other studies have revealed similar results (Alanís, 2000;Senesac, 2002;Lindholm-Leary, 2012). Moreover, Lindholm-Leary (2012) concluded that "Taken together, data from these various studies indicate that [TWI] programs are capable of promoting academic performance for students of different backgrounds, including those subpopulations identified as at risk for academic difficulty" (p. 258).…”
Section: Successes Of Two-way Immersionsupporting
confidence: 49%
See 1 more Smart Citation
“…One representative study found that TWI students outperformed their peers in math and science as well (Marian, Shook, & Schroeder, 2013). Other studies have revealed similar results (Alanís, 2000;Senesac, 2002;Lindholm-Leary, 2012). Moreover, Lindholm-Leary (2012) concluded that "Taken together, data from these various studies indicate that [TWI] programs are capable of promoting academic performance for students of different backgrounds, including those subpopulations identified as at risk for academic difficulty" (p. 258).…”
Section: Successes Of Two-way Immersionsupporting
confidence: 49%
“…Not surprisingly, a number of researchers find that there are many more English language curricular resources than there are resources in Spanish (Amrein & Peña, 2000). Also, because state standardized tests tend to be in English, teachers often spent more time prioritizing instruction in English to help students be in a better position to score highly on such tests (Alanís, 2000). Researchers have also found that even Spanish-dominant students seem to prefer speaking English in peer conversations when the focus was on issues related to popular culture and other student interests (Potowski, 2004).…”
Section: Continuing Challenges Of Two-way Immersionmentioning
confidence: 99%
“…In the 90:10 model, all students are immersed in the minority language first and English is gradually increased until a 50:50 distribution is reached at the upper elementary levels (see Tedick, this issue). Both models can be effective when they are well-implemented: both 50:50 (e.g., Alanís, 2000;Calderón & Carreón, 2000;Cazabon, Nikoladis & Lambert, 1998) and 90:10 models (e.g., Lindholm-Leary, 2001;Lindholm-Leary & Block, 2010) meet their academic, cultural, and English proficiency goals for participating students. Studies have also found, however, that students, who enter the 50:50 model as monolingual English speakers, may not all reach proficiency in Spanish.…”
Section: Twi Program Outcomes: the General Picturementioning
confidence: 97%
“…Studies have also found, however, that students, who enter the 50:50 model as monolingual English speakers, may not all reach proficiency in Spanish. Alanís (2000) found that only 53% of English speakers were proficient by 4th grade. The data in Cazabon et al (1998) show superior achievement in Spanish for TWI Hispanic students when compared to the Anglo students in the program or Hispanic students in a transitional bilingual program.…”
Section: Twi Program Outcomes: the General Picturementioning
confidence: 97%
“…Thus, students in these programs consistently outperform their peers academically (Alanis, 2000;2001;Lopez & Tashakkori, 2004), achieve bilingualism and biliteracy (Genesee, Lindholm-Leary, Saunders, & Christian, 2006), develop favorable attitudes toward bilingualism, the programs, and other cultural groups (Cazabon, Lambert, & Hall, 1993;Lambert & Cazabon, 1994;Lindholm-Leary, 2001), and cultivate a more positive sense of identity (Reyes & Vallone, 2007). Naturally, this compendium of benefits has largely contributed to the expansion of this educational approach in the United States.…”
Section: Introductionmentioning
confidence: 99%